Sex‐Associated Disparities in Surgical and Percutaneous Management of Aortic Stenosis With Severe Features: Retrospective Analysis From the National Readmission Database - Castaldi, Gianluca; Matetić, Andrija; Bagur, Rodrigo; Abbott, J. D.; Alasnag, Mirvat; Chieffo, Alaide; Wijeysundera, Harindra C.; Mamas, Mamas A. (Journal of the American Heart Association, 2025)
Referral for valve intervention for severe aortic stenosis (AS) may exhibit sex-associated disparities independent of the growth of transcatheter interventions. This study aimed to determine whether there were sex-associated differences in the use of aortic valve replacement (AVR), either surgical or transcatheter, in patients with aortic stenosis and severe features from a national cohort of patients. Using the National Readmission Database, all patients with an index diagnosis of AS between January 2015 and December 2019 were included and stratified by their 90-day readmission status and sex. AS with severe features was defined as the combination of primary- or secondary-coded diagnosis of AS in combination with heart failure, syncope, angina pectoris, cardiac arrest, or cardiogenic shock. A 1:1 nested case-control matching was performed to account for competing risk. The main investigated outcome was the sex-associated rate of AVR in the 90 days after index hospitalization. A total of 31 712 matched weighted discharges were included in the analysis, 16 597 men (52.3%) and 15 116 women (47.7%). At 90 days, the rate of AVR was significantly lower in women (45.7% versus 53.6%, <0.001) with significant difference for both surgical ( <0.001) and transcatheter ( =0.010) interventions. After multivariable adjustment, these differences persisted with women significantly less likely to receive AVR (adjusted odds ratio [aOR], 0.67 [95% CI, 0.63-0.71], <0.001), either surgical AVR (aOR, 0.48 [95% CI, 0.43-0.54], <0.001) or transcatheter aortic valve implantation (aOR, 0.79 [95% CI, 0.75-0.84], <0.001). The use of surgical AVR and transcatheter aortic valve implantation was significantly lower in female patients with AS and severe features independent from patient- and hospital-level characteristics.